If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(3x+6)=4(x+7)
We move all terms to the left:
-2(3x+6)-(4(x+7))=0
We multiply parentheses
-6x-(4(x+7))-12=0
We calculate terms in parentheses: -(4(x+7)), so:We get rid of parentheses
4(x+7)
We multiply parentheses
4x+28
Back to the equation:
-(4x+28)
-6x-4x-28-12=0
We add all the numbers together, and all the variables
-10x-40=0
We move all terms containing x to the left, all other terms to the right
-10x=40
x=40/-10
x=-4
| t/5+8=2 | | -3x+7=4x-49 | | 14-2(4-p)=54 | | 3(2-4w)=54 | | 10-{r}{3}=-2 | | 12x-4=9x-2 | | -{k}{5}=4 | | 7x+6=5x+16 | | (2x-4)+x=23 | | 2d+3=5+6d | | {x-1}{4}=6 | | 2w+13w=55 | | 11(x-1)=8x+13 | | 5-a=2a+20 | | 3(2x+5)=4–x | | 18b+11=11 | | 0.4(16+12x)=28 | | 25x-5-12x+3=29x-7-16x+13 | | z-7=9z+1 | | 4(3+6x)-2=58 | | 2x+x=4/7=3 | | (5x+12)+40+x=180 | | 2^2x+3+4^x-16=0 | | 2^2x+3×4^x-16=0 | | (15x-48)+x=180 | | 7h=-2(2h-18) | | x-66=6x-6 | | 12+4m=9.6+8m | | 6/4=9x= | | 1.3(x)-0.3=9 | | 2^x-2=13 | | 90-3x=70-2x |